Model Pengembangan Pariwisata Berkelanjutan pada Daya Tarik Wisata di Kecamatan Gerokgak - Ketut Ayu Puspaningsih; M. Rudi Irwansyah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2025)
The tourism potential in Gerokgak District has a negative impact on social, cultural and environmental impacts. This research aims to identify factors that influence the development of sustainable tourism in Gerokgak District and determine strategies for developing sustainable tourism at tourist attractions in Gerokgak District. The research method used was quantitative using 33 tourism awareness group administrators in Gerokgak District as respondents. The data analysis used is MICMAC and SMICPROB. The results of this research show that the variables in the second quadrant or relay variables have an influential nature but are very dependent, namely natural resource management (psda), employment opportunities (lp), and tourist visits (kw). In the third quadrant or dependent variables which are highly dependent but have little influence, namely people's income. In the fourth quadrant or excluded variables which have little influence and little dependence, namely community participation, waste management, and cultural preservation are factors that influence the development of sustainable tourism in Gerokgak District. Tourism development in Gerokgak District can be carried out with a tourism development strategy with community empowerment.